2011
DOI: 10.1682/jrrd.2010.08.0147
|View full text |Cite
|
Sign up to set email alerts
|

Usability testing of multimodal feedback interface and simulated collision-avoidance power wheelchair for long-term-care home residents with cognitive impairments

Abstract: Abstract-Many older adults in long-term-care homes have complex physical and cognitive impairments and have difficulty propelling manual wheelchairs. Power wheelchair use is restricted owing to safety concerns. Power wheelchairs with collisionavoidance features are being developed to enable safe and independent mobility; however, a paucity of information exists on interface features to help users navigate away from obstacles. We developed a system combining an interface with auditory, visual, and haptic feedba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 49 publications
4
17
0
1
Order By: Relevance
“…Many IPW features such as obstacle avoidance and path following may help to decrease accidents that occur during PW use. This notion is in keeping with previous research where participants in a long-term care facility recognized that collision avoidance would help to prevent accidents [23]. Interestingly, participants in another study suggested that an IPW could be used for training purposes for individuals who are having difficulty learning to drive a PW, which may improve skill and decrease accidents [15].…”
Section: Decreased Risk Of Accidents While Participating In Social Acsupporting
confidence: 82%
“…Many IPW features such as obstacle avoidance and path following may help to decrease accidents that occur during PW use. This notion is in keeping with previous research where participants in a long-term care facility recognized that collision avoidance would help to prevent accidents [23]. Interestingly, participants in another study suggested that an IPW could be used for training purposes for individuals who are having difficulty learning to drive a PW, which may improve skill and decrease accidents [15].…”
Section: Decreased Risk Of Accidents While Participating In Social Acsupporting
confidence: 82%
“…We apply similar techniques to the problem of navigation by combining adaptive prompts with collision avoidance to allow wheelchair users to reach their destination in a safe and timely manner. The study reported in this paper advances other studies with older adults with dementia driving anti-collision wheelchairs [11] [12] by adding a wayfinding component.…”
Section: Related Worksupporting
confidence: 54%
“…Hence, CA technology may provide enhanced opportunities for skills and confidence training. CA technology's potential as an adjunctive training tool for older users has been previously suggested [39]. However, the effectiveness of CA and the recommended protocols to be used in power mobility training with older adults requires further exploration.…”
Section: Power Mobility Driving Concernsmentioning
confidence: 99%